2007
DOI: 10.1016/j.neuron.2007.10.036
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor RDL Inhibits Drosophila Olfactory Associative Learning

Abstract: In both mammals and insects, neurons involved in learning are strongly modulated by the inhibitory neurotransmitter GABA. The GABAA receptor, resistance to dieldrin (Rdl), is highly expressed in the Drosophila mushroom bodies (MBs), a group of neurons playing essential roles in insect olfactory learning. Flies with increased or decreased expression of Rdl in the MBs were generated. Olfactory associative learning tests showed that Rdl overexpression impaired memory acquisition but not memory stability. This lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
165
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 56 publications
12
165
0
Order By: Relevance
“…3A). Knockdown of GABA A receptors by targeted expression of a UAS-RdlRNAi construct (Liu et al, 2007(Liu et al, , 2009; Das et al, 2011) in PNs expressing TRPA1 also similarly blocked habituation induced by exposure to 29°C for 30 min (Fig. 3B).…”
Section: Pn Feedback To Lns Underlies Olfactory Habituationmentioning
confidence: 69%
“…3A). Knockdown of GABA A receptors by targeted expression of a UAS-RdlRNAi construct (Liu et al, 2007(Liu et al, , 2009; Das et al, 2011) in PNs expressing TRPA1 also similarly blocked habituation induced by exposure to 29°C for 30 min (Fig. 3B).…”
Section: Pn Feedback To Lns Underlies Olfactory Habituationmentioning
confidence: 69%
“…Previous reports have shown that downregulation of GABA synthesis in the APL neurons led to enhanced olfactory associative learning in the T-maze paradigm (Liu and Davis, 2009), the same behavioral phenotype produced by knocking down GABA A receptor RDL in the MBs (Liu et al, 2007). Heat punishment was associated with upright T but switched to inverted T upon reversal of stimulus-reinforcement association.…”
Section: The Apl Neurons Are Required For Visual Reversal Learningmentioning
confidence: 73%
“…Flies were reared in standard food vials at 25°C and 60% relative humidity with a 12 h light/dark cycle (Guo et al, 1996). The upstream activating sequence (UAS) strain Rdli8 -10j (Liu et al, 2007) was provided by Dr. R. Davis (The Scripps Research Institute, Jupiter, FL) and the GH146-Gal4 (Stocker et al, 1997) and UAS-TNTE (Sweeney et al, 1995) strains by Z.R. Wang (Institute of Neuroscience, Chinese Academy of Sciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kcc DHS1 stock carrying OK107 (D642) was constructed by first crossing D245 virgin females to a w;;;OK107 stock, then crossing w; 1/ CyO;;OK107/1 male progeny from this cross to homozygous w; kcc DHS1 D506 virgin females and finally combining w; kcc DHS1 / CyO;;OK107/1 male and virgin female progeny from this cross to establish a stock. The MB-GAL80 flies were from Scott Waddell (University of Massachusetts Medical School); flies carrying the Ncc69 RNAi (Dietzl et al 2007) and Rdl RNAi (Liu et al 2007) were obtained from the Bloomington Drosophila Stock Center. Strains carrying kcc DHS1 along with one of these third chromosomal mutations were created as in the same manner as described for the third chromosomal GAL4 driver stocks.…”
Section: Molecular Biologymentioning
confidence: 99%